Assessment of body mass index and spine mobility in children with constitutional hypermobility - Zych, Ewa; Gębska, Magdalena (Journal of Education, Health and Sport, 2018)
Introduction. Hypermobility is a genetic condition that affects the connective tissue. The main symptoms of this syndrome include laxity of joint capsules and ligaments, increased range of movement and pain. Although the condition is genetically determined, different factors may influence the occurrence if symptoms and the intensity of the disorders. Aim. Assessment of body mass index and spine mobility in children with hipermobility of joints. Material and methods. The study included a group of 100 children aged from 6 to 10 years. The presence of hypermobility was determined using Beighton scale. 21 boys and 13 girls with established hypermobility were admitted for the study group. The control group was chosen at random, taking into account the number and sex. The body mass index was additionally examined in all children. The results were plotted on centile grid, suitable for the age and sex of the subjects. The last examination carried out was the assessment of the spine joints mobility. Results. The comparison between the two groups of subjects showed the results were statistically insignificant ( p> 0.05) for BMI values. Statistical analysis showed association (p≤ 0.05) between ranges of spinal movements in particular sections in children with HS only in three movements: slope sideways to the right in the thoracolumbar section, thoracolumbar segment turn to the right and thoracolumbar segment turn to the left.